Enhancing the Conductivity and Thermoelectric Performance of Semicrystalline Conducting Polymers through Controlled Tie Chain Incorporation - Zhu, Wenjin (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 The Authors. Advanced Materials published by Wiley‐VCH GmbH.